Enhanced Oil Recovery: A Future for Pakistan - Dr. Muhannad, Talib Shuker (2012)
This study is an attempt to extrapolate the potential lies in Pakistani reservoir using Enhanced oil recovery methods. This paper presents a methodology for the selection of the enhanced oil recovery technologies that better applies to some group of fields using screening criteria. The methodology has been integrated in software in order to make repetitive analysis in an easier way, and has been applied for identifying the technologies with higher technical potential of application in the Pakistani Fields which has large potential for enhanced oil recovery applications. The methodology incorporates oil and rock properties and the reservoir current conditions, besides the specific knowledge of the reservoir generalities and history. The enhanced oil recovery methods considered in this analysis were: water injection, Water alternating Gas injection (miscible and immiscible), polymer, and surfactant – polymer, steam (cyclic and continuous). The subject discussed in this paper is more significant for companies that own fields with declining production rates and need to identify those with better characteristics for enhanced oil recovery projects in a quick and easy way to improve recovery factors; nevertheless, it is also very useful for companies that are beginning to develop any specific field.